Turismo e interpretação do patrimônio cultural: São Miguel das Missões - Rio Grande do Sul - Brasil - Biesek, Ana Solange (My University, 2014)
Exploratory research on the interpretation of the cultural heritage of São Miguel das Missões (Rio Grande do Sul, Brasil)on the field of cultural tourism. Basead on bibliographical an documental research, in loco visits, observation, data registration of the spot and interviews, with representatives from IPHAN and from the Secretaria Municipal de Turismo. The work, in the theoretical part, deals with conceptual aspects of the cultural heritage and with the relationship between tourism and the interpretation of this heritage. On the field research, the work describes and analyses the ocurrency of the interpretation of the cultural heritage on the spot, based on the interpretative model of Stela Maris Murta and Brian Goodey. It concludes that there is not a plan and the interpretative actions were done in an isolated way. There is a real necessity of a specific cultural and environmental interpretative planning towards the preservation of the heritage, the development of the cultural tourism and the local and regional sustentability. Hence, the work proposes, as a contribution, course of actions.
Pesquisa exploratória sobre a Interpretação do Patrimônio Cultural de São Miguel das Missões (Rio Grande do Sul, Brasil) no âmbito do Turismo Cultural. Baseou-se em levantamento bibliográfico e documental, visitas in loco , observação e registro dos dados do sítio, e entrevistas com representantes do IPHAN e da Secretaria Municipal de Turismo. Na parte teórica trata de aspectos conceituais de Patrimônio Cultural e da relação entre Turismo e Interpretação desse patrimônio. Na pesquisa de campo, descreve e analisa a ocorrência da interpretação do patrimônio cultural no sítio, com base no modelo de plano de interpretação de Stela Maris Murta e Brian Goodey. Conclui que: não há um plano e as ações interpretativas foram implantadas de forma isolada; há necessidade premente de um adequado planejamento interpretativo cultural e ambiental que vise a preservação do patrimônio, o desenvolvimento do turismo cultural e a sustentabilidade local e regional. Para tanto, apresenta propostas norteadoras a título de contribuição.
Keywords: Turismo; Turismo cultural; Interpretação do patrimônio cultural; Planejamento interpretativo; Ocorrência e propostas; São Miguel das Missões; Rio Grande do Sul; Brasil; Cultural tourism; Interpretation of the cultural heritage; Interpretative planning; Ocurrencies and proposals; São Miguel das Missões; Rio Grande do Sul; Brasil